Der Fuchs = The fox [videorecording (DVD)] - Goiginger, Adrian; Morzé, Simon, 1996-; Reinwald, Maximilian; Markovics, Karl, 1963-; Niederhuber, Karola; Kerezovic, Marko; Gradziel, Adriane; Obonya, Cornelius, 1969- (Greenwich Entertainment, 2024)
At the dawn of World War II, a young motorcycle courier in the Austrian army encounters a wounded fox cub and takes it with him to occupied France. The soldier and the fox develop an unlikely bond. Based on the true story of Franz Streitberger, director Adrian Goiginger's great-grandfather.